Digital laser beam stabilizer tank rangefinder sight - Александрова, Татьяна Евгеньевна (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
The article is shown that in the development of fire control systems of modern tanks trend of transition from stabilizing laser rangefinder sight of the power type to a tracer-type stabilizers. The processes of stabilization of the laser beam tank rangefinder sight when using the digital indicator type stabilizer with digital low-frequency filters. It is shown that the best noise immunity of a closed system stabilization can be achieved by using digital filters Butterworth and Lanczos, operating on a series-parallel circuit.